Hantu Jawa sebagai Inspirasi Perancangan Desain Karakter Karakter Video Game Tempa Atma - Novida Nur Miftakhul Arif (Universitas Negeri Semarang, 2024)
Folklore and literary works in Indonesia have the potential to be developed in new forms and expressions that can serve as engaging mediums for conveying messages to the younger generation. Beliefs regarding ghosts among Javanese society can serve as a source for creating works in the current digital era, such as designing character design for a video game. Combined with the study of Kakawin Sena, an ancient literary work from approximately the 16th to 18th centuries, which narrates the story of a knight who fearlessly confronts various challenges embodied in diverse ghosts to achieve his goals. The video game Tempa Atma attempts to utilize the richness of Javanese folklore, namely the belief in Javanese ghosts, and the ancient Indonesian literary work Kakawin Sena as the foundation for designing enemy character design. The method used is divided into two main phases: conceptual (idea generation, goal determination, target audience analysis, data collection, pre-production, production, and post-production) and visualization (sketching, creation of main objects along with coloring, shading, and finishing) carried out digitally. Each enemy character design is crafted by considering the original sources from literary studies, creatively developed while paying attention to the characteristics of the primary target audience, namely elementary school-aged children. It is hoped that the resulting works can compete on the global stage by bringing forth a strong local identity.